Analysis Of The Influence Of PAD and DAU On Capital Expenditure In The Bireuen Regency Government - Safwatul Muna; Qamara Nuzula; M. Reza; Siti Sahar Maulidia; Zurrahmah (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the effect of Regional Original Revenue (PAD) and General Allocation Fund (DAU) on Capital Expenditures in the Government of Bireuen Regency. Capital Expenditures are an important indicator in supporting sustainable regional development. The research uses a quantitative method with a multiple linear regression approach. The data used are secondary data obtained from the regional government financial reports during the 2017–2023 period. The results of the F-test show that PAD and DAU simultaneously have a significant effect on Capital Expenditures, with an F-count value of 9.119 greater than the F-table value of 6.94 and a significance of 0.0032. However, the partial t-test results indicate that only PAD significantly affects Capital Expenditures, with a t-count of 4.185 and a significance of 0.014, while DAU does not show a significant effect, with a t-count of 1.184 and a significance of 0.302. The coefficient of determination (R²) of 0.820 indicates that 82% of the variation in Capital Expenditures can be explained by PAD and DAU. These findings highlight the importance of strengthening local revenue capacity to enhance regional development through capital spending.